Fatty acid composition, enzyme inhibitory, and antioxidant activities of the ethanol extracts of selected wild edible plants consumed as vegetables in the Aegean region of Turkey. Issue 3 (4th March 2017) - Sarikurkcu, Cengiz; Targan, Serif; Ozer, Mehmet Sabih; Tepe, Bektas
ABSTRACT: The aim of this study was to evaluate the fatty acid composition, enzyme inhibitory, and antioxidant activities of the ethanol extracts of selected wild edible plants consumed as vegetable in the Aegean region of Turkey. In general, Mentha piperita L., Rumex patientia L., and R. acetosella L. exhibited quite strong antioxidant activities in the majority of test systems, whereas Urtica dioica L. and Eruca sativa Mill. show quite weak antioxidant activities. Enzyme inhibitory activities of the plants were found quite different than those of their antioxidant activities. Cardaria draba (L.) Desv., E. sativa, R. patientia, and E. cicutarium (L.) L'Hér. showed the highest inhibitory activities on acetylcholinesterase, butyrylcholinesterase, α -amylase, and α -glucosidase, respectively. U. dioica also showed a promising inhibitory activity on these enzymes. In parallel to the experiments, total phenolic, flavonoid, flavonol, and saponin contents of the extracts were also determined. According to the results of these assays, M. piperita had the highest amounts of phenolics, flavonols, and saponins (162.36 mg gallic acid equivalents/g extract, 3.52 mg CEs/g extract and 761.54 mg QAEs/g extract, respectively). Opopanax hispidus (Friv.) Griseb. and Lepidium sativum L. were found to be rich in flavonoid compounds (121.18 and 104.21 mg Res/g extract, respectively). In general, a strong correlation was determined between the phytochemical profile and antioxidant activity of the plant species.